Hypersensitivity Reactions to Components of Cardiac Implantable Electronic Devices and Their Treatment: A Systematic Review - Emma Kealaher; Parin Shah; Tharindra Dissanayake; Dewi E Thomas; James Barry; Andrei D Margulescu (Arrhythmia & Electrophysiology Review)
Background: Hypersensitivity reactions (HSRs) to components of cardiac implantable electronic devices (CIEDs) are rare but difficult to differentiate from device infection. Data on best management strategies of HSRs to CIEDs are lacking. The aims of this systematic review are to summarise the available literature on the aetiology, diagnosis and management of HSR in CIED patients and to provide guidance on best management strategies for these patients. Methods and Results: A systematic search for publications on HSR to CIED in PubMed from January 1970 to November 2022 was conducted, resulting in 43 publications reporting on 57 individual cases. The quality of data was low. The mean age was 57 ± 21 years, and 48% of patients were women. The mean time from implant to diagnosis was 29 ± 59 months. Multiple allergens were identified in 11 patients (19%). In 14 cases (25%) no allergen was identified. Blood tests were mostly normal (55%), but eosinophilia (23%), raised inflammatory markers (18%) and raised immunoglobulin E (5%) were also encountered. Symptoms included local reactions, systemic reactions or both in 77%, 21% and 7% of patients, respectively. Explantation of CIED and reimplantation of another CIED coated with a non-allergenic material was usually successful. Use of topical or systemic steroids was associated with high failure rates. Conclusion: Based on the limited data available, the treatment of choice for HSRs to CIEDs is full CIED removal, reassessment of CIED indication and reimplantation of devices coated in non-allergenic materials. Steroids (topical/systemic) have limited efficiency and should not be used. There is an urgent need for further research in this field.